Motivasi Mahasiswa Dalam Memilih Tourism Sebagai Mata Kuliah Peminatan Pendidikan Bahasa Inggris - Sinta Ari Susanti; Alwi Muhammad; Rizky Rachmawan (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2021)
Covid-19 pandemic impacts to the government's policies in the tourism, namely the tourism restrictions that affect Tourism class to eliminate direct practice in the field. However, the Tourism class is still in demand by the students of English Language Education Islamic State University Raden Mas Said Surakarta until it is divided into two classes. This study aims to determine the motivation of English Language Education students in choosing Tourism as elective course at the fifth semester during the Covid-19 pandemic, though this elective course is no longer offered for the class of 2020. This study used a qualitative approach with a case study method. The research data was collected through interview, observation and documentation. The research used a purposive sampling technique, namely four students of fifth semester of the English Language Education who took Tourism class. The results showed that the motivation of English Language Education students in the fifth semester in choosing Tourism as elective course was divided into two, namely (a) intrinsic motivation, including desire, the needs of learning, interest in the field of Tourism, expectation, self-development, responsibility in completing tasks, cognitive needs, and goal setting and (b) extrinsic motivation, including the encouragement of others, a conducive environment, interesting learning activities, and hygiene factors.